Association of cord blood Nevirapine concentration with reported timing of dose and HIV-1 transmission - Jackson, J. Brooks; Parsons, Teresa; Musoke, Philippa; Nakabiito, Clemensia; Donnell, Deborah; Fleming, Thomas; Mirochnick, Mark; Mofenson, Lynne; Fowler, Mary Glenn; Mmiro, Francis; Guay, Laura (Aids, 2006)
Background: To correlate nevirapine presence and concentration in cord bloods of infants born to HIV-1 infected women with report of timing of dose and HIV-1 transmission at 6 weeks of age. Methods: All available cord blood samples from the infants of mothers enrolled in the HIVNET 012 trial who were randomly assigned to receive either nevirapine or zidovudine at the onset of labor were tested for a nevirapine concentration. Results: Nevirapine was detected in the cord blood of 244 of 259 (94%) infants whose mothers reported they took nevirapine in labor more than 1 h before delivery and in 12 of 13 (92%) infants whose mothers reported they took nevirapine less than 1 h before delivery. The median nevirapine cord blood concentration was 1238 ng/ml [interquartile range (IQR), 905–1474 ng/ml] and 122 ng/ml (IQR, 64–321 ng/ml) for women who reported taking nevirapine more or less than 1 h before delivery, respectively (P < 0.001). The median nevirapine cord blood concentration of infants who were HIV-1 negative at birth, but positive at 6–8 weeks of age (n ¼ 11), was 916 ng/ml (IQR, 737–1245 ng/ml) compared with 1192 ng/ml (IQR, 875–1471 ng/ml) for uninfected infants (n ¼ 236). Conclusions: Cord blood nevirapine concentration correlated well with report of nevirapine administration and timing of dose before delivery. The nevirapine cord blood concentration was modestly lower in infected infants, although the number of infants infected between birth and 6–8 weeks of age was small (n ¼ 11). The high adherence rate in the HIVNET 012 study supports the efficacy, simplicity and deliverability of this regimen.
Keywords: HIV-1; Perinatal transmission; Nevirapine; Cord blood; Uganda; HIVNET 012